The contribution of technology in developing marketing behavior (Al-Academy, 2024)
Marketing is based on a number of factors whose scope extends to diverse ranges, including technology, which has become the effective element in the movement and growth of life and keeping pace with rapid movements in various aspects of life. It is worth noting that all arts and print design provide life with everything that contributes to adapting design capabilities to serve Functional goals, including marketing, promotion, and advertisements, whether for products or services. Therefore, the current research has dealt with technology and its role in an attempt to know its importance, which is concerned with building a mental idea responsible for interpreting the superficial visual appearances of publications of all kinds. The research included two chapters, the first the research problem and its importance, and the following question was How can technology control marketing behavior? The first chapter dealt with the goal of the research, which is revealed by revealing the contribution of technology in developing marketing behavior? The most important terms that are important to the title of the research were identified, and the temporal, spatial, and thematic boundaries were also included. As for the second chapter, it dealt with two sections. The first section included a study of the concept of technology, its types, and its role in print design and marketing and its approved mechanisms. As for the third chapter, it included research procedures, presentation of sample models, and analysis of the research results and conclusions, as well as recommendations, proposals, and a list of sources, and among the most prominent results reached by the researcher